Analisis efektivitas penerimaan pajak hiburan di Kota Jambi periode 2010-2016 - M.Ramadhan Pahlevi; Hardiani Hardiani; Erni Achmad (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
The purpose of this study is to determine and analyze the amount of effectiveness of entertainment tax revenue in Jambi City, to analyze the contribution of entertainment tax to local taxes in Jambi City. The data used is to look at the PAD, especially entertainment tax data which can be taken from the Jambi City Regional Income Tax Office (DISPENDA). Based on the results of the discussion on the effectiveness analysis of the entertainment tax in the city of Jambi, the period 20102-2016 shows that the development of entertainment tax in Jambi City continues. experiencing changes every year. In 2010 amounted to 6.14% from the previous year, the smallest development in 2011 was 6.14% and the largest in 2012 was 66.45%. This research implies that the development of entertainment tax in Jambi City in the 2010-2016 period has an average development of 25.065% of each year. This entertainment tax can be increased again by providing guidance and counseling activities by related parties to owners or managers of entertainment venues in Jambi City to be active in making tax payments and further improving services. Keywords: Effectiveness, Entertainment tax